Development of a dual-arm rapid grape-harvesting robot for horizontal trellis cultivation - Jiang, Yingxing; Liu, Jizhan; Wang, Jie; Li, Wuhao; Peng, Yun; Shan, Haiyong (Frontiers in Plant Science, 2022)
It is extremely necessary to achieve the rapid harvesting of table grapes planted with a standard trellis in the grape industry. The design and experimental analysis of a dual-arm high-speed grape-harvesting robot were carried out to address the limitations of low picking efficiency and high grape breakage rate of multijoint robotic arms. Based on the characteristics of the harvesting environment, such as the small gap between grape clusters, standard trellis and vertical suspension of clusters, the configuration of the dual-arm harvesting robot is reasonably designed and analyzed, and the overall configuration of the machine and the installation position of key components are derived. Robotic arm and camera view analysis of the workspace harvesting process was performed using MATLAB, and it can be concluded that the structural design of this robot meets the grape harvesting requirements with a standard trellis. To improve the harvesting efficiency, some key high-speed harvesting technologies were adopted, such as the harvesting sequence decision based on the "sequential mirroring method" of grape cluster depth information, "one-eye and dual-arm" high-speed visual servo, dual arm action sequence decision and optimization of the “visual end effector” large tolerance combination in a natural environment. The indoor accuracy experiment shows that when the degree of obscuration of grape clusters by leaves increases, the vision algorithm based on geometric contours of grape clusters can still meet the demands of harvesting tasks. The motion positioning average errors of the left and right robotic arms were (X: 2.885 mm, Y: 3.972 mm, Z: 2.715 mm) and (X: 2.471 mm, Y: 3.289 mm, Z: 3.775 mm), respectively, and the average dual-arm harvesting time in a single cycle was 8.45 s. The field performance test verifies that the average harvesting cycle of the robot with both arms reached 9 s/bunch, and the success rate of bunch identification and harvesting success rate reached 88% and 83%, respectively, which were significantly better than those of existing harvesting robots worldwide.